2020
DOI: 10.1002/jia2.25477
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of second‐line antiretroviral therapy among children living with HIV: a global cohort analysis

Abstract: Introduction Limited data describe outcomes on second‐line antiretroviral therapy (ART) among children globally. Our objective was to contribute data on outcomes among children living with HIV after initiation of second‐line ART in the context of routine care within a large global cohort collaboration. Methods Patient‐level data from 1993 through 2015 from 11 paediatric HIV cohorts were pooled. Characteristics at switch and through two years of follow‐up were summarized for children who switched to second‐line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The study also showed that 5 out of 75 participants (6.7%) had been lost to follow-up. This mimicked the cumulative incidence of loss to follow-up (LTFU) at the end of 2 years of follow-up among similar cohorts in sub-Saharan Africa (7.1%) versus less than 5% globally, reported by the Collaborative Initiative for Paediatric HIV Education and Research (CIPHER) Global Cohort Collaboration [ 26 ].…”
Section: Discussionmentioning
confidence: 62%
“…The study also showed that 5 out of 75 participants (6.7%) had been lost to follow-up. This mimicked the cumulative incidence of loss to follow-up (LTFU) at the end of 2 years of follow-up among similar cohorts in sub-Saharan Africa (7.1%) versus less than 5% globally, reported by the Collaborative Initiative for Paediatric HIV Education and Research (CIPHER) Global Cohort Collaboration [ 26 ].…”
Section: Discussionmentioning
confidence: 62%
“…In addition, TAF-containing regimens have been demonstrated to be a not-to-be-ignored strategy for children ( O'Rourke et al, 2023 ). When second-line ART is begun in children, their CD4+ T lymphocyte count increases, and their mortality and loss to follow-up decrease ( Collaborative Initiative for Paediatric HIV Education and Research (CIPHER) Global Cohort Collaboration, 2020 ). Consequently, treating drug resistance in children is positively impacted by prompt medication modifications.…”
Section: Resultsmentioning
confidence: 99%